Degradation of Carbamazepine in Aqueous Solution Using Ozanation Process - Khadijeh Darabi; Abooalfazl Azhdarpoor; Mansoureh Dehghani (Shiraz University of Medical Sciences, 2019)
Background: Carbamazepine is a pharmaceutical compound used as an anticonvulsant for epilepsy and can enter the environment by inappropriate treatment of hospital wastewater. Therefore, the present study aimed to investigate the removal of carbamazepine from the aquatic environment, using the ozonation process. Methods: This is an experimental study in which certain concentrations of carbamazepine were removed, using the ozonation process. The effect of such factors as pH (3-11), carbamazepine concentration (5-15 ppm), ozone dose (200-400 mg/hr), and reaction time (15-180 seconds) on the removal efficiency was studied. Data analysis was performed to measure carbamazepine, using the High-Performance Liquid Chromatography (HPLC). Results: The results showed that the carbamazepine removal efficacy at pHs of 5, 7, and 11 was 81%, 66%, and 21%, respectively at 15 ppm, the reaction time of 30 seconds, and the ozone dose of 200 mg/hr, respectively. Also, at the dose of 200 and 400 mg/hr injectable ozone at pHs of  5 and 7, removal efficiency was 81%, 66%, 97%, and 78%, respectively. Conclusion: According to the results, at pH=5, reaction time of 30 seconds, the carbamazepine concentration of 15 ppm, injectable ozone dose of 200 mg/h, a removal efficiency of 81% was obtained. The ozonation process can react directly or indirectly with the drug contaminant in very low concentrations in aqueous solutions due to its high oxidation power, leading to its destruction or elimination, which may indicate that the ozonation method may be used as an effective method to remove carbamazepine and other similar contaminants.